Improvement of The System of Labor Motivation at An Industrial Enterprise - Liudmila NADREEVA; Vladimir ABRAMOV (Communications of International Proceedings, 2021)
In modern conditions the problems of personnel motivation are especially important for particular enterprises, because the quality of labor potential and the extent of its realization determines the competitiveness of the enterprise, its ability to compete in the market. This article presents the results of the analysis of the existing system of personnel motivation management at one of the Tatarstan enterprises. The diagnostics of the personnel motivation and stimulation system was performed by means of questionnaires, the factors, influencing the enterprise personnel motivation, the SWOT - analysis of the motivation system of the investigated enterprise was conducted. Based on the results of the study, there were developed recommendations and proposed measures for improving the system of motivation and stimulation of personnel.
Keywords: Motivation; motivational attitudes; personnel management; job satisfaction; material incentives; non-material incentives.